Insights into enhancing Centella asiatica organ cell biofactories via hairy root protein profiling - Alcalde, Miguel Angel; Hidalgo-Martinez, Diego; Bru Martínez, Roque; Sellés-Marchart, Susana; Bonfill, Mercedes; Palazon, Javier (Frontiers in Plant Science, 2023)
Recent advancements in plant biotechnology have highlighted the potential of hairy roots as a biotechnological platform, primarily due to their rapid growth and ability to produce specialized metabolites. This study aimed to delve deeper into hairy root development in C. asiatica and explore the optimization of genetic transformation for enhanced bioactive compound production. Previously established hairy root lines of C. asiatica were categorized based on their centelloside production capacity into HIGH, MID, or LOW groups. These lines were then subjected to a meticulous label-free proteomic analysis to identify and quantify proteins. Subsequent multivariate and protein network analyses were conducted to discern proteome differences and commonalities. Additionally, the quantification of rol gene copy numbers was undertaken using qPCR, followed by gene expression measurements. From the proteomic analysis, 213 proteins were identified. Distinct proteome differences, especially between the LOW line and other lines, were observed. Key proteins related to essential processes like photosynthesis and specialized metabolism were identified. Notably, potential biomarkers, such as the Tr-type G domain-containing protein and alcohol dehydrogenase, were found in the HIGH group. The presence of ornithine cyclodeaminase in the hairy roots emerged as a significant biomarker linked with centelloside production capacity lines, indicating successful Rhizobium-mediated genetic transformation. However, qPCR results showed an inconsistency with rol gene expression levels, with the HIGH line displaying notably higher expression, particularly of the rolD gene. The study unveiled the importance of ornithine cyclodeaminase as a traceable biomarker for centelloside production capacity. The strong correlation between this biomarker and the rolD gene emphasizes its potential role in optimizing genetic transformation processes in C. asiatica.